In the Infinite Pool: The Cinematic Spectatorship of Sleep Has Her House (2017). Issue 3 (23rd March 2023) - Dzhitenov, Sloane
Scott Barley's Sleep Has Her House is a recent landmark of experimental cinema, combining recent trends in the landscape and slow cinema movements to produce a painstakingly crafted meditation on nature and the viewer's gaze upon it. Characterized by its manipulation of light and temporality, the film draws upon the various modes of viewing established by preceding experimental movements, as exemplified by the work of Warhol, Deleuze, and Brakhage, amongst others, to test the relationship between viewer and viewed. The film's further environmental concerns, as filtered through its landscape focus, are explored through the recent writings of Plumwood, Kimmerer, and Heidegger and their concerns with animacy and human–nature relations. The result is a film that tests the relationship between man and environment through its manipulation of viewing and seeing, prompting a more animate and holistic view of the natural world.